System transformation in central and Eastern Europe, economic development and subjective well‐being - Macewicz, Jakub J. (Creativity Studies, 2010)
One of the vital questions connected with the system transformation in Poland and other former Soviet Bloc countries is whether the overthrow of the communist system was caused by the poor state of their economies or rather people’s struggle for their civil rights. However, the “either/or nature” of this question is disturbed by another possibility: it might have been a relatively good state of the economy which made the overthrow possible. Moreover, there is no doubt that the introduction of free market and democracy resulted in many positive changes in people’s lives: from the increase in life expectancy and subjective well‐being to the growth of civil liberty. Yet, economic development and (more broadly) modernity also produce extensively described negative effects which, at certain point, seem to “neutralise” their positive ones. Poland and other Central and Eastern European countries seem to follow this path. Sistemos transformacija vidurio ir Rytų Europoje, ekonomikos plėtra ir subjektyvioji gerovė Santrauka. Vienas svarbiausių klausimų, susijusių su sistemos transformacija Lenkijoje ir kitose buvusiose sovietinio bloko šalyse, yra toks – ar komunistinio režimo nuvertimas buvo sukeltas neturtingų valstybių ekonomikos, ar žmonių kovos dėl savo teisių? Kad ir kaip būtų, šio klausimo atsakymui „arba... arba“ trukdo kita galimybė: tai galėtų būti gera valstybė, kurios ekonomika sudarė palankias sąlygas nuversti minėtą režimą. Be to, nėra abejonių, kad laisvos rinkos ir demokratijos įvedimas sukėlė daug pozityvių pokyčių žmonių gyvenime – nuo didėjančių galimybių ir gerovės iki augančios pilietinės laisvės. Vis dėlto ekonomikos plėtra ir modernumas taip pat sukelia plačiai aprašytų negatyvių pasekmių, kurios tam tikrais atvejais naikina pozityviąsias. Lenkija ir kitos Vidurio bei Rytų Europos šalys eina šiuo keliu. Reikšminiai žodžiai: sistemos transformacija, kapitalizmas, ekonomikos augimas, laimė, tradicinės ir sekuliariosios bei racionaliosios vertybės, materialinės ir postmaterialinės vertybės, subjektyvioji gerovė. First published online: 10 Feb 2011